Geo-Electric Resistivity Method of Dipole-Dipole Configuration For Cavities Model 2D in Karst Area of Temurejo Village Gubug Sub-district Central Java District - Yuanna Rhesdeantia; Teguh Darsono; Khumaedi Khumaedi (Journal of Physics: Theories and Applications, 2017)
The purpose of this research is to mapping cavities in karst area in Temurejo Village, Karangrayung, Grobogan using geoelectric resistivity method and dipole-dipole configuration. Measurement consist of six lines using Multichannel S-Fields geoelectric instrument. Apparent resistivity data processing use two software, Res2DInv ver. 3.56.22 and Voxler 4.0. The result is lithology of the research location can be interpret consist of sand-silt, carbonate-silt rock, carbonate-sand rock, and carbonate rock with resistivity range 15,3-4919 Ωm. There are resistivity value anomaly in line of 1,2,3,4,5, and 6 on the carbonate rocks layer, the value is more than 4949 Ωm which can interpret as a cavity. On the first line, cavities are at depths of 20 m and 12 m, on second line are at depths of 17 m and 12 m, on third line is at depth of 19 m. Cavity continuously at depth of 18 m on fourth, fifth and sixth lines. This cavities at the depth >23 m beneath eath surface.